2006
DOI: 10.1111/j.1753-4887.2006.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Foods: Products for the Management of Chronic Diseases

Abstract: Medical foods are a specific category of therapeutic agents created under the Orphan Drug Act of 1988, which separated medical foods from drugs for regulatory purposes. Products in this category share the requirements that they are intended for the nutritional management of a specific disease, are used under the guidance of a physician, and contain ingredients that are generally recognized as safe (GRAS). An example of medical foods are formulations intended to manage patients with inborn errors in amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Genistein is considered a class 2 compound with low solubility and high permeability by the FDA's Biopharmaceutics Classification System. Though there are no formal requirements for this type of analysis of medical foods or supplements, it is important that fasting and fed PK and bioequivalence studies be performed, especially since medical foods have a statutory requirement to be indicated for a specific disease and must be administered under the direction of a physician [21]. Indeed, a fasting and fed PK study of genistein has been performed on the medical food Fosteum indicated for osteopenia/osteoporosis suggesting a minor, nonstatistical effect of food on absorption [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genistein is considered a class 2 compound with low solubility and high permeability by the FDA's Biopharmaceutics Classification System. Though there are no formal requirements for this type of analysis of medical foods or supplements, it is important that fasting and fed PK and bioequivalence studies be performed, especially since medical foods have a statutory requirement to be indicated for a specific disease and must be administered under the direction of a physician [21]. Indeed, a fasting and fed PK study of genistein has been performed on the medical food Fosteum indicated for osteopenia/osteoporosis suggesting a minor, nonstatistical effect of food on absorption [31].…”
Section: Discussionmentioning
confidence: 99%
“…The FDA-regulated, prescription medical food [21], Fosteum, for the clinical dietary management of osteopenia and osteoporosis under physician supervision was formulated in collaboration with Squadrito and coworkers as previously described [11, 12]. The OTC bone supplement, Citracal Plus Bone Density Builder, is based on a bone support formula already on the market (Citracal) and uses literature support to justify the addition of genistein [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…467 Medical foods are not drugs and, thus are not subject to any regulatory requirements that apply to drugs. Thus, medical foods do not have to undergo premarket review or approval.…”
Section: Medical Foodsmentioning
confidence: 99%
“…41 Through a 5-step process, AAB prevents deamination by the liver, promotes uptake into the appropriate neuron, conversion to the neurotransmitter, releases the adenosine brake, and prevents the attenuation of effect. Medical foods 42 are specially formulated products for the specific dietary management of a disease or condition that has distinctive nutritional requirements. Nutrient imbalances caused by pain leads to metabolic disequilibrium.…”
Section: Introductionmentioning
confidence: 99%